2011
DOI: 10.1523/jneurosci.0580-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Attentional Modulation of fMRI Responses in Human V1 Is Consistent with Distinct Spatial Maps for Chromatically Defined Orientation and Contrast

Abstract: Attending to different stimulus features such as contrast or orientation can change the pattern of neural responses in human V1 measured with fMRI. We show that these pattern changes are much more distinct for colored stimuli than for achromatic stimuli. This is evidence for a classic model of V1 functional architecture in which chromatic contrast and orientation are coded in spatially distinct neural domains, while achromatic contrast and orientation are not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
(67 reference statements)
1
3
0
Order By: Relevance
“…The ratio between the response amplitude to the luminance (L) and chromatic (C) components of the compound grating was unimodally distributed and pronouncedly biased towards luminance (mean L/C = 4.31 in V1 linear cells), indicating that V1 responds ∼4 times more robustly to the luminance than to chromatic contrast (∼2 times if the luminance contrast is equalized to the chromatic cone contrast). The luminance/color preference of V1 linear neurons was correlated with their OS, a finding that adds a novel perspective to an ongoing discussion on the neuronal encoding of color and orientation in the primary visual cortex (Livingstone and Hubel 1984;Johnson et al 2001Johnson et al , 2008Gegenfurtner 2003;Economides et al 2011;Song et al 2011). We also demonstrate that V1 cells associated with positive LFPs in deep cortical layers (the subcortical output of area V1) show stronger combined responses to luminance and color than other V1 cells.…”
Section: Discussionsupporting
confidence: 59%
“…The ratio between the response amplitude to the luminance (L) and chromatic (C) components of the compound grating was unimodally distributed and pronouncedly biased towards luminance (mean L/C = 4.31 in V1 linear cells), indicating that V1 responds ∼4 times more robustly to the luminance than to chromatic contrast (∼2 times if the luminance contrast is equalized to the chromatic cone contrast). The luminance/color preference of V1 linear neurons was correlated with their OS, a finding that adds a novel perspective to an ongoing discussion on the neuronal encoding of color and orientation in the primary visual cortex (Livingstone and Hubel 1984;Johnson et al 2001Johnson et al , 2008Gegenfurtner 2003;Economides et al 2011;Song et al 2011). We also demonstrate that V1 cells associated with positive LFPs in deep cortical layers (the subcortical output of area V1) show stronger combined responses to luminance and color than other V1 cells.…”
Section: Discussionsupporting
confidence: 59%
“…Second, in posterior brain areas, the target region of attentional control, attention to some specific stimulus dimension increases the level of baseline activity in the corresponding sensory region, even when visual stimulation is kept constant (Martinez-Trujillo & Treue, 2004; Serences, Saproo, Scolari, Ho, & Muftuler, 2009; Song, Rowland, McPeek, & Wade, 2011). …”
Section: Identifying General Principles Underlying Conscious and Uncomentioning
confidence: 99%
“…Neuroimaging studies in human participants showed that perceiving a cue that indicates what will be the relevant dimension of the target is associated first with increased activity in prefrontal areas ( Bode & Haynes, 2008 ; Hopfinger, Buonocore, & Mangun, 2000 ; Hopfinger, Woldorff, Fletcher, & Mangun, 2001 ). Second, in posterior brain areas, the target region of attentional control, attention to some specific stimulus dimension increases the level of baseline activity in the corresponding sensory region, even when visual stimulation is kept constant ( Martinez-Trujillo & Treue, 2004 ; Serences, Saproo, Scolari, Ho, & Muftuler, 2009 ; Song, Rowland, McPeek, & Wade, 2011 ).…”
Section: Identifying General Principles Underlying Conscious and Uncomentioning
confidence: 99%
“…Even within a particular age group, there is remarkable inter-individual variability in anatomy both at the level of whole tissue volume/thickness and cortical morphology. For example, brain volume across 30 individuals aged (18–35) was found to vary by as much as 40% (Song et al, 2011). Cortical gyri-sulci morphology (contours, folding patterns, functional localization) are complex and are characterized by high inter-individual variability (Mangin et al, 2004; Derrfuss et al, 2009).…”
Section: Introductionmentioning
confidence: 99%